Primary chronic osteomyelitis of the jaw - a descriptive study of the condition and its occurrence in Sweden between 2012 and 2018 - Caroline Robertsson; Carina Cardemil (Medical Journals Sweden, 2024)
Purpose: Primary chronic osteomyelitis (PCO) of the jaw is a non-infectious, inflammatory state of the jawbone of unknown etiology.  This study aimed to investigate the occurrence of PCO in Sweden between the years 2012 and 2018, the characteristics of the condition, treatment methods, and outcomes.  Material and methods: The search for patients with PCO in Sweden 2012-2018 was performed at 24 oral and maxillofacial surgery units in Sweden. Results: During this 6-year period, 17 patients were identified as diagnosed with PCO in Sweden. The mean age was 10.6 years at diagnosis, and the female:male ratio was 4:1. Conclusion: We conclude that PCO is a very rare disease in Sweden, and that standardized, well-defined criteria are necessary to calculate incidence rates but also to increase knowledge about etiology, clinical characteristics, and treatment outcomes in rare conditions such as PCO.